Patterns of physical activity and health-related quality of life amongst patients with multimorbidity in a multi-ethnic Asian population - Mythily Subramaniam; Yunjue Zhang; Jue Hua Lau; Janhavi Ajit Vaingankar; Edimansyah Abdin; Siow Ann Chong; Eng Sing Lee (BMC, 2019)
Abstract Background The co-occurrence of two or more chronic medical conditions in an individual is defined as multimorbidity. Lifestyle factors, including poor dietary patterns, physical inactivity, tobacco use, and excessive alcohol consumption are key modifiable risk factors that play a role in the development of chronic medical conditions and potentially multimorbidity. The current study aimed to examine the level of physical activity among those with multimorbidity and its association with socio-demographic factors, clinical parameters, and health-related quality of life (HRQoL) among community-dwelling adults attending a primary care clinic in Singapore. Methods This cross-sectional study was conducted among patients with multimorbidity between August 2014 and June 2016. Physical activity was measured using the International Physical Activity Questionnaire (IPAQ) Short Form. HRQoL was measured using the EuroQol-5 Dimension (EQ-5D-3 L). Data on clinical parameters including hemoglobin A1c (HbA1C), low-density lipoprotein cholesterol (LDL-C), and blood pressure were collected from patient records. Multivariable logistic regression analysis and linear regression were performed to determine the association between IPAQ and clinical health outcomes, as well as HRQoL measures, respectively. Results In all, 932 respondents with multimorbidity were recruited for the study. Of these, 500 (53.8%) had low physical activity, 325 (35.0%) had moderate physical activity, while 104 (11.2%) had high physical activity. Respondents who were insufficiently active had significantly higher odds of being overweight/ obese (OR: 1.5, 95% confidence interval [CI]: 1.1-1.9, p = 0.01) as compared to those who were sufficiently physically active. The multiple linear regression model revealed that insufficient activity level was negatively associated with EQ-5D index score (β = − 0.05, p <  0.001) and the visual analogue scale (β = − 4.4, p <  0.001) measuring HRQoL as compared to sufficient activity levels in respondents with multimorbidity. Conclusions The low levels of physical activity among patients with multimorbidity, and its association with overweight status and poorer HRQoL emphasizes the importance of increasing physical activity in this population. Family physicians treating patients with chronic diseases need to continue encouraging and helping individuals to initiate and maintain appropriate physical activity levels.